2022
DOI: 10.4103/jiaps.jiaps_67_22
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Management of Retained Double-J Stents in Children During the Coronavirus Disease-2019 Pandemic

Abstract: Background: Double-J (DJ) stents were commonly used for internal drainage after major reconstructive procedures or in cases of obstruction and ureteral injuries. They should be removed or changed within the stipulated time; otherwise, they can lead to various complications such as stent occlusion, migration, breakage, encrustation, stone formation at either end of the stent, and entanglement of the two stents if bilateral stenting was done. The present study focuses on the complications and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Retained DJ stents can occur due to several reasons, including patient noncompliance, lack of proper follow-up, failure to remove the stent, and technical difficulties during insertion or removal. The most common reason for retained stents are patient noncompliance, accounting for approximately 40% of cases [3] . Another study reported that around 25% of patients did not receive adequate information about the importance of stent removal, resulting in delayed or failed removal.…”
Section: Discussionmentioning
confidence: 99%
“…Retained DJ stents can occur due to several reasons, including patient noncompliance, lack of proper follow-up, failure to remove the stent, and technical difficulties during insertion or removal. The most common reason for retained stents are patient noncompliance, accounting for approximately 40% of cases [3] . Another study reported that around 25% of patients did not receive adequate information about the importance of stent removal, resulting in delayed or failed removal.…”
Section: Discussionmentioning
confidence: 99%